Optimization for Reduction of NOx and Heat Loss of Parawood Chips Boiler Process Combined with Air Preheater and Controller Using Aspen Dynamics - Jirateep Premsuksatian (Faculty of Engineering, Chiang Mai University, 2020)
Engineering Journal Chiang Mai University